Public administration an action orientation - Denhardt, Robert B.; Grubbs, Joseph W. (Wadsworth, Cencage Learning, 2014)
Encourages students to become active participants in public administration. This title helps readers teach how to influence the operations of public agencies - helping them learn to get involved and effect positive changes, regardless of whether they are working outside the agency as citizens or within the agency as managers